Drought, Wellbeing and Adaptive Capacity: Why Do Some People Stay Well? - Austin, Emma K. (Int J Environ Res Public Health, 2020)
Drought is a threat to public health. Individual and community adaptive capacity is crucial when responding to the impacts of drought. Gaps remain in the understandings of the relationship between wellbeing and adaptive capacity, and whether increased wellbeing can lead to improved adaptive capacity (or vice versa). This paper explores the relationship between drought, wellbeing and adaptive capacity to provide insights that will inform actions to enhance adaptive capacity, and hence increase opportunities for effective drought adaptation. The theory of salutogenesis and the associated sense of coherence (SOC) are used to measure adaptive capacity and to explain why some individuals remain well and adapt to adversity while others do not. An online survey of rural residents (n = 163) in drought-affected New South Wales (NSW), Australia, was conducted from November 2018 to January 2019. Linear regression was used to model the relationships between SOC, sociodemographic factors, drought and wellbeing. Findings demonstrate that SOC is strongly correlated with wellbeing. Drought condition did not influence adaptive capacity, although adaptive capacity and drought-related stress were only weakly correlated. Increased wellbeing was found to be associated with stronger adaptive capacity and therefore, an individuals’ capacity to cope with adversity, such as drought.